2022
DOI: 10.3389/fcimb.2022.894644
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Recruitment in Pneumococcal Pneumonia

Abstract: Streptococcus pneumoniae (Spn) is the primary agent of community-acquired pneumonia. Neutrophils are innate immune cells that are essential for bacterial clearance during pneumococcal pneumonia but can also do harm to host tissue. Neutrophil migration in pneumococcal pneumonia is therefore a major determinant of host disease outcomes. During Spn infection, detection of the bacterium leads to an increase in proinflammatory signals and subsequent expression of integrins and ligands on both the neutrophil as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 138 publications
0
21
0
Order By: Relevance
“…While neutrophils are a crucial part of the host defense, on the other hand, an excessive neutrophil response may be disadvantageous and further aggravate lung injury and lead to systemic bacteriemia 57,58 . In line with this, Ang‐2 (angiotensin‐2), an endothelial mediator known to be increased in patients with severe pneumonia, 59 was found to suppress clock modulator Rev‐Erbα mRNA and protein expression in THP‐1 macrophages in a dose‐ and time‐dependent manner, thereby reducing the production of barrier disrupting enzyme matrix metalloprotease 9 60 .…”
Section: The Role Of Circadian Rhythms In the Lungsmentioning
confidence: 84%
“…While neutrophils are a crucial part of the host defense, on the other hand, an excessive neutrophil response may be disadvantageous and further aggravate lung injury and lead to systemic bacteriemia 57,58 . In line with this, Ang‐2 (angiotensin‐2), an endothelial mediator known to be increased in patients with severe pneumonia, 59 was found to suppress clock modulator Rev‐Erbα mRNA and protein expression in THP‐1 macrophages in a dose‐ and time‐dependent manner, thereby reducing the production of barrier disrupting enzyme matrix metalloprotease 9 60 .…”
Section: The Role Of Circadian Rhythms In the Lungsmentioning
confidence: 84%
“…with a specific A1 receptor inhibitor (whose specificity we confirmed in prior publications 28,34 ) or vehicle control. Mice were then infected intratracheally with 2.5x10 4 As CXCR2 was reported to be required for trans-endothelial migration in response to pneumococcal infection 11,14,[35][36][37] , we directly assessed the role of A1 on PMN transendothelial migration. Young mice were treated i.p.…”
Section: A1 Receptor Signaling Is Required For Pmn Pulmonary Influx I...mentioning
confidence: 99%
“…We further found that while A1 receptor inhibition had no effect of CD18 expression (Fig 8C), it significantly lowered CXCR2 expression at 6 hpi (Fig 8D),the time point at which PMN influx to the lungs is lowered (Fig8A). As CXCR2 was reported to be required for trans-endothelial migration in response to pneumococcal infection11,14,[35][36][37] , we directly assessed the role of A1 on PMN trans-endothelial migration. Young mice were treated i.p.…”
mentioning
confidence: 99%
“…250 Memory AMs express major histocompatibility complex (MHC)-II and chemokines at higher levels, and show more glycolysis and bacterial killing. 4,203,[249][250][251] Infection-induced IIM has been associated with molecules such as NOD2; possibly viral RNA; and proteins containing a leucine-rich repeats (LRR)-containing domain are evolutionarily conserved in many proteins associated with innate immunity. 252 Similarly, NLRP3 (NOD-, LRR-and pyrin domain-containing protein 3), which is an intracellular sensor that detects many microbial molecules may also be associated.…”
Section: Infectious Diseasesmentioning
confidence: 99%